Digestibility of diets with dehydrated citrus pulp for fattening rabbits - Rubio Varela, Juliana Alejandra (2023)
The aim of this study was to evaluate the nutritional composition and in vitro digestibility in rabbits of a pelleted feed using citrus pulp as a substitute for a conventional feed. It was used 24 adult rabbits (>80 days) distributed in four treatments (0, 10, 20 and 30%) with six repetitions. The experimental period was 12 days (7 for the adaptation period and 5 for the faeces collection). The orange pulp presented 7.4% crude protein (CP), 14.9% crude fibre (CF), 3.8% ether extract, 5.1% mineral matter, 4308 kcal/kg of gross energy and 385.76 mg polyphenols per 100 g of citrus pulp. CP levels decreased as the inclusion level of citrus pulp increased (16.77 to 17.85%), while the dry matter digestibility percentage increased with higher pulp inclusion levels. It is concluded that up to 30% of citrus pulp can be included in rabbit feed as a substitute for commercial concentrate without affecting nutrient digestibility.